Synthesis and Characterization of Mobile Crystalline Material-41 Doped with Titanium and Iron - Bao-Wang Lu; Zheng-Ming Wang; Takahiro Hirotsu (Adsorption Science & Technology)
Titanium-doped mobile crystalline material-41s (MCM-41s) and Fe- and Ti-doped MCM-41s were synthesized by direct thermal synthesis at moderate Ti and small Fe doping amounts, and their structural and porous properties were examined by X-ray diffraction, nitrogen adsorption, and ultraviolet-visible absorption techniques. It was found that a moderate Ti addition condition is required to introduce Ti species into the framework of silica walls without losing the regular mesoporous structure. Further Fe incorporation into Ti-doped MCM-41 modifies the mixed phase–doped structure and shifts the absorption edge to the visible light range. By appropriately choosing synthesis conditions, it is possible to incorporate both Ti and Fe in MCM-41 without sacrificing the ordered mesoporosity and the high specific surface area while greatly improving the light absorption properties.